1988
DOI: 10.1136/bmj.296.6624.765
|View full text |Cite
|
Sign up to set email alerts
|

The objective structured interview for medical student selection

Abstract: An objective structured interview is an integral part of the process of selecting and admitting applicants to study medicine at this university. During the nine years (to the end of 1986) that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 23 publications
5
108
1
Order By: Relevance
“…It was hypothesised that the qualities that the respondents rated as most important would be comparable to those that the admissions process was attempting to identify. The qualities being measured (Powis et al 1988) by the JMP admissions process are highlighted in Table 2.…”
Section: Desirable Qualitiesmentioning
confidence: 99%
“…It was hypothesised that the qualities that the respondents rated as most important would be comparable to those that the admissions process was attempting to identify. The qualities being measured (Powis et al 1988) by the JMP admissions process are highlighted in Table 2.…”
Section: Desirable Qualitiesmentioning
confidence: 99%
“…However, the use of an interview to assist selection of graduate students can be problematic and results recorded in the literature have been mixed. One study has demonstrated that an objective structured interview, when used as part of the overall selection process, can have significant predictive validity (Powis et al, 1988). This study showed that an interview can predict which students failed to complete the course and which students achieved honours.…”
Section: Discussionmentioning
confidence: 97%
“…7 It also fi ts with data which indicate an inverse relationship between broader, noncognitive parameters such as experience in leadership positions and a likelihood of failure. 8,9 There is undoubtedly controversy about the reliability of interviews in the student selection process, but this is a global view representing a broad range of interview techniques. When considered in greater detail, strategies which have a highly structured format, and which employ trained interviewers, have a greater predictive value when it comes to assessing an individual's 'non-cognitive' strengths.…”
Section: Discussionmentioning
confidence: 99%